Pengaruh Price Fairness Dan Perceived Service Quality Terhadap Customer Satisfaction Pada Jasa Grabcar Di Kota Bandung - De Silva, Muh.Janward Sawanawadu; Rubiyanti, R. Nurafni (eProceedings of Management, 2024)
Ride-hailing has become one of the fastest-growing transportation services in Indonesia, making it an increasinglypopular and widely used transportation alternative, with its use predicted to continue increasing. One of thecompanies offering its services in the online transportation sector in Indonesia is Grab. The purpose of this researchis to determine the effect of price fairness and perceived service quality on customer satisfaction with GrabCarservices. The research used a descriptive quantitative method. The sample for the study consists of 150 individuals,collected through a Google Forms questionnaire. The research sample was obtained using non-probability samplingwith a purposive sampling technique. The analysis technique used is multiple linear regression. The results of thestudy show that price fairness and perceived service quality, both partially and simultaneously, have a significanteffect on customer satisfaction, accounting for 85.1%, while the remaining 14.9% is influenced by other variables notincluded in the study.Keywords-price fairness, perceived service quality, consumer satisfaction